Designing a Chatbot-Enabled Laptop Diagnostic Assistant - Muhamad Sapiee, Muhammad Hariz; Mokhtar, Rashidah; Abd Rahman, Mazlyda; Mutalib, Sofianita; Suhaimi, Azrina (Journal of Soft Computing and Data Mining, 2022)
This paper proposes a chatbot developed with deep learning techniques to help people troubleshoot operating system errors in laptops. In today's world, people can't wait for anything and expect an immediate response when they have a question because they want their problems solved quickly and completely. The system addresses the software aspect of technical laptop issues concerning a laptop's operating system. Deep learning is used to create the chatbot because it has been shown to be more accurate in selecting its response when conversing with users. The chatbot will be integrated into Telegram, an instant messaging service, and users will be able to communicate about laptop issues via Telegram.